Electrolytic Generation of Oxygen Partially Explains Electrical Enhancement of Tobramycin Efficacy against Pseudomonas aeruginosa Biofilm - Stewart, Philip S. (American Society for Microbiology, 1999)
The role of electrolysis products, including protons, hydroxyl ions, reactive oxygen intermediates, oxygen, hydrogen, and heat, in mediating electrical enhancement of killing of Pseudomonas aeruginosa biofilms by tobramycin (the bioelectric effect) was investigated. The log reduction in biofilm viable cell numbers compared to the numbers for the untreated positive control effected by antibiotic increased from 2.88 in the absence of electric current to 5.58 in the presence of electric current. No enhancement of antibiotic efficacy was observed when the buffer composition was changed to simulate the reduced pH that prevails during electrolysis. Neither did stabilization of the pH during electrical treatment by increasing the buffer strength eliminate the bioelectric effect. The temperature increase measured in our experiments, less than 0.2°C, was far too small to account for the greatly enhanced antibiotic efficacy. The addition of sodium thiosulfate, an agent capable of rapidly neutralizing reactive oxygen intermediates, did not abolish electrical enhancement of killing. The bioelectric effect persisted when all of the ionic constituents of the medium except the two phosphate buffer components were omitted. This renders the possibility of electrochemical generation of an inhibitory ion, such as nitrite from nitrate, an unlikely explanation for electrical enhancement. The one plausible explanation for the bioelectric effect revealed by this study was the increased delivery of oxygen to the biofilm due to electrolysis. When gaseous oxygen was bubbled into the treatment chamber during exposure to tobramycin (without electric current), a 1.8-log enhancement of killing resulted. The enhancement of antibiotic killing by oxygen was not due simply to physical disturbances caused by sparging the gas because similar delivery of gaseous hydrogen caused no enhancement whatsoever.